Two Distinct Back-Arc Closure Phases of the East Sea: Stratigraphic Evidence From the SW Ulleung Basin Margin - Lee, Jae-Hyuk; Lee, Jae-Ho; Yoon, Seok-Hoon; Lee, Hyun-Suk; Song, Hoon-Young; Kim, Gi-Bom (Frontiers in Earth Science, 2022)
This study focuses on revisiting the tectostratigraphic framework of the Ulleung Basin and conceptualizing neotectonics around the western East Sea margin. Based on the analysis of 2D and 3D multi-channel seismic reflection data and offshore drill wells, we divided the entire sedimentary successions of the Ulleung Basin into four tectostratigraphic sequences, named TS1 (c. 23–16 Ma), TS2 (c. 16–9 Ma), TS3 (c. 9–4 Ma), and TS4 (c. 4 Ma–present), in ascending order. The results show that each sequence has been deformed once or multiple times in different periods by juxtaposing two major compressional structures named the Dolgorae Thrust-Fold Belt and the Gorae Anticline. Interpretation of the stratal deformation and termination patterns of the syn- and post-deformational sequences of each structures suggests that the thrusting and folding of the Dolgorae Thrust-Fold Belt was active from c. 16 Ma to c. 9 Ma under the NNW–SSE compressional stress regime (Stage-2), whereas the Gorae Anticline was active from 4 Ma to the present under the ENE–WSW compressional stress regime (Stage-4). Between these two compressional events, there was an intervening period of regional slow subsidence driven by thermal contraction of the back-arc lithosphere and isostatic sedimentary loading (Stage-3). Based on the stratigraphic and structural reconstruction, we propose a 4-stage tectonic model: Stage-1) back-arc opening stage associated with the southward drift of the Japanese islands (c. 23–16 Ma), Stage-2) tectonic-inversion stage in association with the reorganization of the Pacific and Philippine Sea plates and clockwise rotation of SW Japan (c. 16–9 Ma), Stage-3) post-inversion stage with regional thermal and isostatic subsidence (c. 9–4 Ma), and Stage-4) neotectonic stage in which embryonic subduction is nucleating on the East Sea margins under the E–W compressional stress regime (c. 4 Ma–present).